Diagnosis and Treatment planning for Implant-Supported Fixed Prosthesis (Journal of Dhaka National Medical College & Hospital, 2012)
Implant prosthodontics were introduced in 1980s. Most unsuccessful cases are the result of a lack of communicating among the team members, insufficient knowledge of each members responsibilities, false assumptions etc. Understanding failures and their causes is more difficult with implant-supported prosthesis than with conventional prosthodontics. Careful diagnosis and treatment planning with a team approach prior to implant placement can help ensure a successful outcome. Diagnosis and treatment planning for use of a implant-supported fixed prosthesis are essential. The prognosis of the treatment plan should be confirmed by the implant team prior to treatment. All team members should understand the desired goals. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12194 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 47-52